The Influence of Rewards and Work Environment on Loyalty through Job Satisfaction among Teachers at SMKS Batujaya District (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effect of rewards and work environment on teacher loyalty with job satisfaction as an intervening variable in private vocational schools in Batujaya District. The study uses a quantitative approach through a questionnaire survey with 82 respondents, determined through nonprobability sampling. The data were analyzed using instrument testing, classical assumption testing, hypothesis testing, and path analysis with the help of SPSS version 26. The results showed that rewards (X1) had a positive and significant effect on job satisfaction (Z) with a t-value of 3.130 > t-table 1.990 and a significance of 0.002 < 0.05. The work environment (X2) also has a positive and significant effect on job satisfaction, as evidenced by a t-value of 10.554 > 1.990 and a significance level of 0.000 < 0.05. Conversely, rewards do not have a significant effect on loyalty (Y) with a t-value of 0.588 < 1.990 and a significance level of 0.558 > 0.05, nor does the work environment with a t-value of 0.168 < 1.990 and a significance level of 0.867 > 0.05. Job satisfaction was proven to have a significant positive effect on loyalty with a t-value of 3.472 > 1.990 and a significance level of 0.001 < 0.05. Path analysis shows that the direct effect of rewards on loyalty is only 0.062, while the indirect effect through job satisfaction is greater at 0.122. Similarly, the work environment has a direct effect of 0.026 and an indirect effect of 0.412. These results confirm that job satisfaction plays an important role as a mediator. Thus, this study emphasizes that a proportional increase in rewards and the creation of a conducive work environment can improve job satisfaction, which ultimately strengthens teacher loyalty at private vocational schools in Batujaya District.